Studying BDNF/TrkB Signaling: Transcriptome Analysis from a Limited Number of Purified Adult or Aged Murine Brain Neurons - Vatanashevanopakorn, C; Grover, A; Nath, A; Clark, K; Sopp, P; Nerlov, C; Minichiello, L (Springer, 2017)
It is recognized by now that the basal ganglia contain some of the circuits most vulnerable to age-related effects. However, it is still unknown how these changes are regulated during aging. We have recently shown that loss of TrkB signaling in striatopallidal enkephalinergic (ENK+) neurons lead to age-dependent spontaneous hyperlocomotion, associated with reduced striatopallidal activation, demonstrating that BDNF-TrkB signaling in striatal ENK+ neurons contributes to the inhibitory control of locomotor behavior exerted by the indirect pathway. Hence, we have established a unique mouse model that provides a rare example of an age-dependent locomotor defect. Identification of the genes and associated molecular pathways relevant to the maintenance of locomotor control requires systematic, unbiased gene expression profiling of the aging striatal circuit from young adult and aged mouse brain, both in normal and TrkB-deficient conditions. For this purpose, we have chosen whole transcriptome analysis by RNA sequencing (RNA-Seq) that offers higher resolution than other methods. To achieve this we have established a protocol that allows for the isolation of fluorescently labeled neurons from adult (3 months) or aged (8 months) mouse brain for whole transcriptome analysis by RNA-Seq using a limited number (<200) of neurons. Neuronal subsets were genetically labeled in vivo with a fluorescent marker and isolated using a sucrose artificial cerebrospinal fluid (aCSF) solution and differential centrifugation before fluorescent activated cell sorting (FACS)-based purification. This was followed by direct cDNA synthesis using an optimized Smart-Seq method, resulting in the generation of robust libraries for Illumina sequencing. In contrast to previous methods used for neuronal gene profiling, this protocol can be used for high-throughput gene expression profiling from limited numbers of adult or aged brain neurons at moderate costs. The whole protocol described here takes 3–4 days from neuronal purification to preparation of cDNA libraries ready for Illumina sequencing.